Improving Math Learning Outcomes on Number Material through Problem Based Learning for 7th Grade Students - Irmadani Parapat; Mhd Yusuf; Hanifah Parapat (CV. Alfa Pustaka, 2026)
Mathematics learning outcomes among junior high school students remain a concern, particularly in understanding the concept of numbers and applying numerical operations in problem-solving situations. Students often experience difficulties in connecting mathematical concepts with contextual problems due to learning activities that are less focused on active exploration and problem-solving. Therefore, this study was conducted to address the need for an instructional approach that could improve students’ understanding and achievement in mathematics learning, particularly on the topic of numbers. This study aimed to describe the improvement of Grade VII students’ mathematics learning outcomes through the implementation of the Problem-Based Learning model. The study employed a Classroom Action Research design involving 30 Grade VII students. Data were collected through learning outcome assessments consisting of quizzes and assignments after the learning activities. The collected data were analysed using descriptive statistical analysis to determine students’ achievement and learning mastery. The results showed that the implementation of the Problem-Based Learning model supported students’ mathematics learning outcomes on the topic of numbers. Students achieved an average final score of 81.82, and 28 students (93.33%) reached the Minimum Mastery Criterion. Furthermore, students demonstrated consistent performance in understanding number concepts, performing numerical operations, and solving mathematical problems. These findings indicated that Problem-Based Learning provided meaningful learning experiences that encouraged students to actively participate, explore mathematical concepts, and develop problem-solving skills. This study implied that Problem-Based Learning could be applied as an alternative instructional strategy to improve mathematics learning outcomes at the junior high school level.